2016
DOI: 10.1039/c5cc09676f
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a non classic host guest complexation mode in a β-cyclodextrin/propionic acid model

Abstract: A non-classic complexation mode was discovered upon spectroscopic, thermodynamic, crystallographic and computational studies of a β-cyclodextrin/propionic acid complex. A "fully immersed" complexation phenomenon, where both the guest's hydrophobic and polar moieties are located inside the host and are stabilized by it, was found and calculated as the most favorable configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…For one, metallo-CDs host-guest systems are oen dynamic, with a fast equilibrium between the hosted and free guest states. In addition, guest molecules may have multiple orientations inside the host's cavity, [31][32][33] creating different carceroisomers, 34,35 or they may bind the host in various host : guest stoichiometries 36 that complicate the analysis of titration data. 37 Furthermore, it was demonstrated that metallo-CD host could deform from its native CD shape or may have the metal center in different positions relative to the CD cavity.…”
Section: Introductionmentioning
confidence: 99%
“…For one, metallo-CDs host-guest systems are oen dynamic, with a fast equilibrium between the hosted and free guest states. In addition, guest molecules may have multiple orientations inside the host's cavity, [31][32][33] creating different carceroisomers, 34,35 or they may bind the host in various host : guest stoichiometries 36 that complicate the analysis of titration data. 37 Furthermore, it was demonstrated that metallo-CD host could deform from its native CD shape or may have the metal center in different positions relative to the CD cavity.…”
Section: Introductionmentioning
confidence: 99%
“…They possess a hydrophobic cavity that can selectively bind substrates and catalyze chemical reactions through formation of host–guest complexes via noncovalent interactions. , The selective functionalization of cyclodextrins offers unique opportunities for chemists, from achieving solubility in a desired solvent to selective and specific catalysis. For example, applications such as drug formulation and controlled release studies require highly water-soluble cyclodextrins and random conversion of hydroxyl groups to amino groups can result in antimicrobial cyclodextrins …”
Section: Introductionmentioning
confidence: 99%
“…Cyclodextrins (CDs), as a model of the host molecule in supramolecular chemistry, are well-known macrocyclic oligosaccharides consisting of α-(1,4) linked glucose units [ 6 , 7 ]. They are inexpensive, water-soluble natural products, non-toxic, easily functionalized, and commercially available, and have been widely used as artificial enzymes, chiral separators, chemical sensors, and drug excipients [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ], owing to their hydrophobic and chiral interiors [ 15 , 16 , 17 ]. Due to their remarkable inclusion capabilities with small organic molecules, more recent interests focus on organic reactions catalyzed by cyclodextrins.…”
Section: Introductionmentioning
confidence: 99%